Stakeholders' views on the strengths and weaknesses of maternal care financing and its reform in Georgia - Lela Shengelia; Milena Pavlova; Wim Groot (BMC, 2017)
Abstract Background The improvement of maternal health has been one of the aims of the health financing reforms in Georgia. Public-private relationships are the most notable part of the reform. This study aimed to assess the strengths and weakness of the maternal care financing in Georgia in terms of adequacy and effects. Methods A qualitative design was used to explore the opinions of key stakeholders about the adequacy of maternal care financing and financial protection of pregnant women in Georgia. Women who had used maternal care during the past 4 years along with health care providers, policy makers, and representatives of international partner organizations and national professional body were the respondents in this study. Six focus group discussions to collect data from women and 15 face-to-face in-depth interviews to collect data from the other stakeholders were conducted. Each focus group discussion consisted of 7-8 women. Two focus group discussions were carried out at each of the target settings (i.e. Tbilisi, Imereti and Adjara). Women were selected in each location through the hospital registry and snowballing method. Results The evidence shows that there is a consensus among maternal care stakeholder groups on the influence of the healthcare financing reforms on maternal health. Specifically, the privatization of the maternal care services has had positive effects because it significantly improved the environment and technical capacity of the maternity houses. Also, in contrast to other former-soviet republics, there are no informal payments anymore for maternal care in Georgia. However the privatization, which was done without strict regulation, negatively influenced the reform process and provided the possibility to private providers to manipulate the formal user fees in maternal care. Stakeholders also indicated that the UHC programs implemented at the last stage of the healthcare financing reform as well as other state maternal health programs protect women from catastrophic health care expenditure. Conclusion The results suggest a consensus among stakeholders on the influence of the healthcare financing reform on maternal healthcare. The total privatization of the maternal care services has had positive effects because it significantly improved the environment and the technical capacity of the maternity house. However, the aim to improve maternal health and to reduce maternal mortality was not fully achieved. Financial protection of mothers should be further studied to identify vulnerable groups who should be targeted in future programs.